Lactate-to-albumin ratio and albumin-corrected anion gap as predictors of outcome in methanol poisoning: A retrospective observational study - İlter Ağaçkıran; Merve Ağaçkıran (PLoS ONE, 2025)
Background Methanol poisoning is a serious condition with high morbidity and mortality, mainly due to its metabolism to toxic formic acid. Laboratory findings, particularly albumin-corrected anion gap (ACAG) and lactate-to-albumin ratio (LAR), can lead critical in assessing the severity of toxicity. This study aims to evaluate the prognostic significance of ACAG, lactate-to-albumin ratio and other laboratory markers in methanol poisoning and to assess the impact of admission time on patient outcome. Methods A retrospective observational study was conducted in a tertiary emergency department. Patients aged ≥18 years presenting with suspected methanol poisoning between January 2020 and December 2023 were included. Diagnosis was based on the American Academy of Clinical Toxicology (AACT) treatment criteria combined with metabolic acidosis and a suggestive history. Clinical and laboratory parameters were compared between good outcome (CPC = 1) and poor outcome (CPC ≥ 2, including deaths) groups. Results Forty-two patients were included. The mean age was 43.45 years and 95.2% were male. The mortality rate was 35.7%. Among patients with poor outcome (n = 17), 15 died and 2 survived with severe neurological sequelae. Patients with poor outcomes had significantly lower pH and bicarbonate levels and higher AG, ACAG, lactate, and creatinine levels (p < 0.001). ACAG ≥25.6 and LAR ≥ 1.24 were the strongest prognostic markers for poor prognosis. Hypotension and osmolar gap differences were noted but were evaluated only as supportive indicators of severity. Conclusion ACAG and LAR can lead useful prognostic markers in methanol poisoning. Patients with ACAG ≥25.6 or LAR ≥ 1.24 should be closely monitored and considered for early intensive management.